Spatially resolved in vivo plant metabolomics by laser ablation-based mass spectrometry imaging (MSI) techniques: LDI-MSI and LAESI - Bartels, Benjamin; Svatoš, Aleš (Frontiers in Plant Science, 2015)
This short review aims to summarize the current developments and applications of mass spectrometry-based methods for in situ profiling and imaging of plants with minimal or no sample pre-treatment or manipulation. Infrared-laser ablation electrospray ionization (LAESI) and UV-laser desorption/ionization (LDI) methods are reviewed. The underlying mechanisms of the ionization techniques - namely, laser ablation of biological samples and electrospray ionization - as well as variations of the LAESI ion source for specific targets of interest are described.